2020
DOI: 10.31866/2616-7468.3.2.2020.219708
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Craft Technology of Boiled Sausage “Firm Plus”

Abstract: Актуальність. Серйозні зміни у структурі харчування, пов'язані з перемінами у способі життя, зменшенням енерговитрат, призводять до того, що жодна із груп населення не отримує зі споживаної їжею необхідної для здоров'я кількості основних поживних речовин та мікро-і макроелементів. Вирішити проблему оптимізації харчування можуть збагачені, так звані полікомпонентні м'ясні продукти. Одним із перспективних напрямів виробництва полікомпонентних м'ясних продуктів є введення до складу стандартних рецептур додаткових… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Such studies of the SPDS «Neoselen» were carried out by the authors earlier and showed its practical safety. This is confirmed by previous research results [6][7][8][9][10][11][12][13][14]. Also the perspective of using the protein isolate obtained from vetch seeds (Vicia sativa L.) by pHshifting treatment had been proved.…”
Section: Introductionsupporting
confidence: 87%
“…Such studies of the SPDS «Neoselen» were carried out by the authors earlier and showed its practical safety. This is confirmed by previous research results [6][7][8][9][10][11][12][13][14]. Also the perspective of using the protein isolate obtained from vetch seeds (Vicia sativa L.) by pHshifting treatment had been proved.…”
Section: Introductionsupporting
confidence: 87%
“…We also investigated the technological parameters of the dietary supplement (Prymenko et al, 2021) and conducted medical and biological studies on it (Holovko et al, 2018). Furthermore, we modeled and developed recipes for food products using the dietary supplement and determined the quality indicators of the finished products (Helikh et al, 2020;Sefikhanova et al, 2020;). An increase in the fat emulsifying and fat retention capacities was observed in the tested product samples (Prymenko et al, 2021).…”
Section: The Topicality Of the Problemmentioning
confidence: 99%
“…Protein isolates of various vegetable crops are widely used to replace traditional raw materials in recipes of yogurts [14] and sausages [15]. Pea proteins have been found suitable for preparing gluten-free muffins with characteristics comparable to those made using wheat gluten [16].…”
Section: Introductionmentioning
confidence: 99%